Behaviour during Malolactic Fermentation of Three Strains of Oenococcus oeni Used as Direct Inoculation and Acclimatisation Cultures - Izquierdo Cañas, P.M.; Romero, E.García; Martín, F. Pérez; Prieto, S. Seseña; Manso, J.M. Heras; Herreros, M.L. Palop (South African Journal of Enology and Viticulture, 2016)
The behaviour in malolactic fermentation (MLF) of an autochthonous strain of Oenococcus oeni, C22L9, isolated from a winery in Castilla-La Mancha (Spain), and of two other commercial strains of O. oeni, PN4 and Alpha (Lallemand Inc.), inoculated by direct inoculation (MBR®) and after a short acclimatisation phase (1-STEP®), was studied. Strain C22L9 carried out MLF slightly faster than the two other commercial strains, leading to a lower increase in volatile acidity and in 2,3-butanedione and 3-hydroxy-2-butanone concentrations, a higher lactic acid content, lower degradation of citric acid and increased degradation of ethanol. No great differences were observed in the duration of MLF, although the acclimatisation cultures were slightly faster, or in the composition of the wines when using the O. oeni strains in the form of MBR® or 1-STEP® cultures. The tasters did not detect significant differences in the wines obtained from the same strain of O. oeni in the two inoculation formats.